Immunopathogenesis of inflammatory bowel diseases: functional role of T cells and T cell homing - Zundler, Sebastian; Neurath, Markus (Clinical and Experimental Rheumatology, 2015)
Inflammatory bowel diseases (IBD) are believed to arise from a complex interplay of environmental factors, genetic susceptibility, epithelial barrier defects and dysregulation of the intestinal immune system. Although the exact mechanisms of contribution and interference of these players are still not clear, significant advances have been achieved in understanding the immunopathogenesis of IBD in recent years resulting in novel and targeted therapeutic strategies. We will begin this review by giving a brief outline of current pathogenetic concepts of IBD and then focus on the description of the present knowledge of T cell function and regulation in the context of IBD. Moreover, we will summarise the progress on the emerging field of gut homing and delineate some implications for future therapeutic approaches.
EVALuna2:1978